The Effect of Leadership Style, Educational Supervision, and Self-Regulation on Teachers' Teaching Ability - Jemmy Jemmy*; Andika Febrianto; Zikri Zaman (Riwayat: Educational Journal of History and Humanities, 2023)
The quality of education in the Northern Minahasa District is a challenge that needs to be overcome to achieve the educational development goals that have been set. According to the findings of the Central Statistical Authority (BPS), there are several factors that cause the low academic performance of students in the district. To address this problem, the study aims to examine the influence of leadership styles, educational supervision, and self-regulation on the teaching abilities of teachers in elementary schools. The research method used was regression analysis using a sample of 112 teachers in 6th grade from the Basic School in the Northern Minahasa district, which came from a population of 155 teachers. The results of the regression analysis show that there is a very strong and significant influence of leadership style variables on teacher teaching abilities. Each increase of one unit in leadership style results in an increase in teacher teaching skills of 1,145 units. Education supervision also has a significant influence but is not as strong as leadership style, with a coefficient of -0.028. Furthermore, self-regulation also has a significant influence, with a coefficient of -0.493. The analysis also shows that leadership styles, educational supervision, and self-regulation together have a significant impact on teachers' teaching abilities. These findings show that it is important for school leaders to pay attention to effective leadership styles in order to motivate and improve the quality of teacher teaching abilities. In addition, it is necessary to enhance the implementation of scheduled and thorough educational supervision to support the professional development of teachers. Self-regulation is also an important factor in improving the quality of teaching, so attention needs to be given to the self-development of teachers .